A Supported Employment linkage intervention for people with schizophrenia who want to work: a survey of patients' views. (April 2015) - Solar, Ann
Objective: Take into account patient views in developing a linkage intervention to the evidence-based Individual Placement and Support approach to Supported Employment (SE) for patients with schizophrenia on a mental health unit (MHU) who want to work in competitive employment. Methods: Analysis of 20 once-off, face-to-face interviews, with informed consent, between author and voluntary MHU inpatients with schizophrenia about getting into SE from the MHU. Results: From the major category 'patient ideas about SE linkage intervention from MHU' the three themes of 'patient choice', 'type of support' and 'start from the MHU' emerged. The other major category, 'patient attitude to the author's proposed SE linkage intervention', revealed the theme of 'positive attitude'. Conclusions: There may be enough interest from patients with schizophrenia on a MHU who want to work, to test a pilot of the author's proposed voluntary SE linkage intervention.